Fiscal Dominance and Inflation in the Democratic Republic of the Congo - Nachega, Jean-Claude (IMF Working Papers; Working Paper, 2005)
This paper examines the fiscal dominance hypothesis in the Democratic Republic of the Congo (DRC) during 1981-2003, using multivariate cointegration analysis and vector errorcorrection modeling. Empirical results point to strong and statistically significant long-run relationships between budget deficits and seigniorage, and between money creation and inflation. The long-run inflationary impact of budget deficits is robust to the inclusion of output growth or velocity in the inflation and monetary growth equations. The paper offers some policy recommendations for long-term price stability in the DRC.